2020
DOI: 10.3390/cells9102229
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Surveys of Iron Homeostasis Mechanisms Reveal Ferritin Superfamily and Nucleotide Surveillance Regulation to be Modified by PINK1 Absence

Abstract: Iron deprivation activates mitophagy and extends lifespan in nematodes. In patients suffering from Parkinson’s disease (PD), PINK1-PRKN mutations via deficient mitophagy trigger iron accumulation and reduce lifespan. To evaluate molecular effects of iron chelator drugs as a potential PD therapy, we assessed fibroblasts by global proteome profiles and targeted transcript analyses. In mouse cells, iron shortage decreased protein abundance for iron-binding nucleotide metabolism enzymes (prominently XDH and ferrit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 187 publications
(240 reference statements)
0
10
0
Order By: Relevance
“…More importantly, RRM2 has been identified as a member of the ferric iron-binding ferritin-superfamily [ 19 ]. Shen et al have demonstrated that RRM2 engaged in the iron metabolism in hepatocellular carcinoma (HCC) [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, RRM2 has been identified as a member of the ferric iron-binding ferritin-superfamily [ 19 ]. Shen et al have demonstrated that RRM2 engaged in the iron metabolism in hepatocellular carcinoma (HCC) [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Genes with expression change ≥ 1.4-fold and assembled data of four sets with a p value < 0.05 were selected for follow-up studies, and 15 genes ( Atf5, Trib3, Nexn, Mt1, Casp4, Hmox1, Bfsp2, Gcg, Ppic, Cdh3, Slc22a8, Ppfibp2, Slc7a11, Bdh2, C1qtnf5 ) were chosen for next analysis. Then, we checked the relevant literature to find the following five up-regulated genes as differentially expressed transcripts in the eyes treated with NK-4 that are related to anti-apoptosis: heme oxygenase 1 ( Hmox1) [ 28 ], metallothionein-1 (Mt1) [ 29 , 30 ], solute carrier family 7 member 11 (Slc7a11) [ 31 ], 3-hydroxybutyrate dehydrogenase 2 (Bdh2) [ 32 , 33 ], and activating transcription factor 5 (Atf5) [ 34 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Bdh2 is expressed in all cell types in the retina to control iron homeostasis [ 32 ]. Bdh2 inhibition was found to result in cellular iron accumulation [ 33 ]. In the present study, we found that Bdh2 was up-regulated in NK-4-injected eyes, indicating that NK-4 may up-regulate the expression of Bdh2 to protect retina and RPE from damage by reducing excessive iron in the retina of RCS rats.…”
Section: Discussionmentioning
confidence: 99%
“…[29]Animal experiments revealed that iron de ciency decreased the expression of RRM2 and reduced the protein abundance of RRM2. [30]And RRM2 may inhibit ferroptosis. [31] The expression level of CCNB1 was abnormally elevated in HCC and high expression is associated with better prognosis, as an oncogene, CCNB could inhibit the apoptosis of HCC cells and promote cell invasion.…”
Section: Discussionmentioning
confidence: 99%